PENGEMBANGAN SISTEM KENDALI OTOMATIS PEMOTONG PISANG BERBASIS ARDUINO MENGGUNAKAN SENSOR LOAD CELL MENINGKATKAN KONSISTENSI PRODUKSI - Muhammad dandy (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Banana chip production in Micro, Small, and Medium Enterprises (MSMEs) is generally still carried out using manual cutting processes. This method has several drawbacks, including inconsistent slice thickness, relatively long processing time, low productivity, and a high risk of hand injuries due to continuous use of knives. In addition, direct contact with banana sap reduces operator comfort and process hygiene. This study aims to design and develop an Arduino Uno-based automatic banana slicing control system to improve cutting efficiency, produce more consistent slice thickness, and enhance operator safety. The research method includes hardware and software design, system assembly, Arduino Uno microcontroller programming, and performance testing using Kepok bananas as the test material. The developed system consists of an Arduino Uno as the main controller, a stepper motor as the driving mechanism, and two limit switches as motion-limiting sensors. Signals from the limit switches are processed by the Arduino to automatically control the rotation direction of the stepper motor, enabling the pusher mechanism to move forward and backward repeatedly during the cutting process. The experimental results show that the proposed system is capable of producing banana slices with a consistent thickness ranging from 1 to 3 mm, regardless of the operator's hand strength. In addition to improving the uniformity of the slices, the system also reduces the risk of hand injuries and minimizes direct contact with banana sap. Based on the results, the Arduino Uno-based automatic control system effectively improves work efficiency, productivity, cutting quality, and operator safety, making it suitable for implementation in banana chip production processes in MSMEs.